Coaching-Based Academic Supervision to Improve Teachers’ Competence in Managing I2m3-Oriented Learning Processes - Ni Putu Sudani; Dewa Gede Hendra Divayana; Anak Agung Gede Agung (Journal of Education Action Reseach, 2026)
Low teacher competence in designing and implementing interactive, inspiring, enjoyable, challenging, and motivating learning remains a challenge in improving instructional quality. This study aims to analyze and examine the effectiveness of coaching-based academic supervision in enhancing teachers’ competence in managing learning processes. The study employed a school action research design conducted in three cycles, consisting of planning, action, observation, and reflection stages. The participants were junior secondary school teachers. Data were collected through observation of lesson planning documents, classroom observation, and structured interviews using observation sheets and interview guidelines. The data were analyzed using descriptive quantitative and qualitative techniques by comparing results across cycles. The findings reveal a consistent improvement in teachers’ competence in each cycle, both in lesson planning and instructional implementation. The application of coaching-based supervision promoted critical reflection, professional autonomy, and continuous improvement in teaching practices. These findings imply that coaching-based academic supervision can serve as a systematic strategy in teacher development programs to enhance learning management quality and strengthen a reflective culture in schools.